DEVELOPMENT OF METHOD FOR DETERMINING THE THERMODYNAMIC AND KINETIC PARAMETERS OF DECOMPOSITION SUBSTANCES IN THE FORM OF THE POWDER MIXTURE WITH HIGHLY THERMALLY CONDUCTIVE INERT MATERIAL BY DIFFERENTIAL SCANNING CALORIMETRY ON THE EXAMPLE OF PARACETAMOL AND CHLORAMPHENICOL - A. V. Ponomareva; A. V. Dudkin (Разработка и регистрация лекарственных средств)
Development of method for determining the melting enthalpy of monotropic transitions and the activation energy of substances decomposition using highly thermally conductive inert material by differential scanning calorimetry and its practical use for determining the weight content of the active substance in solid medicinal substance.